HS-SPME-GC-MS metabolomics approach for sperm quality evaluation by semen volatile organic compounds (VOCs) analysis. (8th November 2018) - Longo, Valentina; Forleo, Angiola; Provenzano, Sara Pinto; Coppola, Lamberto; Zara, Vincenzo; Ferramosca, Alessandra; Siciliano, Pietro; Capone, Simonetta
Abstract: It is estimated that about the 12% of world's couples are infertile, and half of these infertility cases are due to male factors. The main conditions that can affect male fertility are asthenozoospermia and oligozoospermia. For the first time, we analysed semen headspace in order to characterize the pattern of Volatile Organic Compounds (VOCs) in human seminal fluid and to identify specific metabolites that may be potential biomarkers of pathological conditions. By headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) method, we detected both endogenous and exogenous compounds that form a complex mix of metabolites with a high inter-individual biological variability. Nevertheless, it was possible to point out the interconnection between some VOCs and asthenozoospermia and/or oligozoospermia. Furthermore, this work emphasizes the importance of semen as matrix for metabolomic studies that usually focus on other biological fluids.